2017
DOI: 10.1093/annonc/mdx353
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system relapse of diffuse large B-cell lymphoma in the rituximab era: results of the UK NCRI R-CHOP-14 versus 21 trial

Abstract: BackgroundCentral nervous system (CNS) relapse of diffuse large B-cell lymphoma (DLBCL) is associated with a dismal prognosis. Here, we report an analysis of CNS relapse for patients treated within the UK NCRI phase III R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine and prednisolone) 14 versus 21 randomised trial.Patients and methodsThe R-CHOP 14 versus 21 trial compared R-CHOP administered two- versus three weekly in previously untreated patients aged ≥18 years with bulky stage I–IV DLBCL (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 25 publications
8
65
1
4
Order By: Relevance
“…with an estimated 10-year cumulative risk of 28.3%, which is comparable to that of primary testicular DLBCL. 28,29 Notably, in contrast to the general observation that CNS relapse in DLBCL occurred early (median, 6.7-8.1 months), [30][31][32][33] the PB-DLBCL patients in our study showed a persistent risk of CNS relapse occurring up to 8.2 years after initial diagnosis (median, 3.1 years). In addition, our study showed for the first time that synchronous bilateral breast involvement was significantly associated with a higher risk of early CNS progression compared with patients with unilateral breast disease.…”
Section: -Year Os For Pb-dlbcl Patients Treated With R-chop Vs Chopcontrasting
confidence: 91%
See 1 more Smart Citation
“…with an estimated 10-year cumulative risk of 28.3%, which is comparable to that of primary testicular DLBCL. 28,29 Notably, in contrast to the general observation that CNS relapse in DLBCL occurred early (median, 6.7-8.1 months), [30][31][32][33] the PB-DLBCL patients in our study showed a persistent risk of CNS relapse occurring up to 8.2 years after initial diagnosis (median, 3.1 years). In addition, our study showed for the first time that synchronous bilateral breast involvement was significantly associated with a higher risk of early CNS progression compared with patients with unilateral breast disease.…”
Section: -Year Os For Pb-dlbcl Patients Treated With R-chop Vs Chopcontrasting
confidence: 91%
“…Multivariate analyses of predictive factors for progression-free survival (PFS) and overall survival (OS) in Chinese patients with primary breast diffuse large B-cell lymphoma without IT prophylaxis. This finding is in line with several other studies of DLBCL that suggested the inadequate efficacy of intrathecal prophylactic chemotherapy in preventing CNS disease 30,32,33. As brain parenchymal relapse was more common than leptomeningeal relapse in PB-DLBCL, a more promising option would be systemic CNS chemotherapy prophylaxis such as high-dose i.v.…”
supporting
confidence: 88%
“…Half of these patients (2% of all analyzed patients) showed new central nervous system involvement, which is in line with previously reported data (2%-8%). 22,23 Overall, the involvement of initially not affected sites at relapse in the current analysis indicates the necessity of a full imaging at relapse. should be considered as an imaging modality in future studies.…”
Section: Discussionmentioning
confidence: 79%
“…In 5 of the DHSNHL trials, prophylaxis was mandated for patients with bone marrow, testicular or head and neck lymph nodesinvolvement [13] while in the United Kingdom National Cancer Research Institute [UK NCRI]trial, prophylaxis was given to patients with bone marrow, peripheralblood, nasal/paranasal sinuses, orbit and testicular involvement [6].…”
Section: Resultsmentioning
confidence: 99%
“…Using the standard combination chemo-immunotherapy RCHOP regimen [rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone], 70% of cases are expected to be cured, while 30% will have refractory or relapsed disease [3.4]. Although relapse in the central nervous system [CNS] is relatively rare, occurring in about [2-4%] [5,6],it is a devastating event with a median survivalof usually less than 6 months [7.8].…”
Section: Introductionmentioning
confidence: 99%